2016
DOI: 10.4172/2157-7579.1000383
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus: Isolation, Identification and Antimicrobial Resistance in Dairy Cattle Farms, Municipal Abattoir and Personnel in and Around Asella, Ethiopia

Abstract: A cross sectional study was conducted between February, 2014 and April, 2014 to isolate and identify Staphylococcus from dairy cattle farms and municipal abattoir; and to evaluate antimicrobial sensitivity for isolates in and around Asella, Ethiopia. An over all of 181 samples were collected and processed from nine dairy cattle farms (87) and seven municipal abattoir visits (94). Accordingly, 42 (23.2%) udder milk, 9 (5.0%) tank milk, 9 (5.0%) polled bucket swab, 9 (5.0%) tank swab, 9 (5.0%) polled hand swab,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 24 publications
(19 reference statements)
4
19
2
Order By: Relevance
“…But this finding is higher than the findings observed in Taiwan reported 11.3% by Jyhshiun et al, (2009) that isolated S. aureus strains from pork carcass and by Bitaw et al (2010) who reported 20.3% S. aureus isolated from dairy farms in Bahir Dar town and its environment.. The current result was in agreement with the study carried out in Ethiopia, Abunna et al (2017) reported 41% of the isolation rate of S. aureus from samples that were taken from dairy farm as well as abattoir of beef cattle.…”
Section: Discussionsupporting
confidence: 91%
“…But this finding is higher than the findings observed in Taiwan reported 11.3% by Jyhshiun et al, (2009) that isolated S. aureus strains from pork carcass and by Bitaw et al (2010) who reported 20.3% S. aureus isolated from dairy farms in Bahir Dar town and its environment.. The current result was in agreement with the study carried out in Ethiopia, Abunna et al (2017) reported 41% of the isolation rate of S. aureus from samples that were taken from dairy farm as well as abattoir of beef cattle.…”
Section: Discussionsupporting
confidence: 91%
“…All the selected studies were cross-sectional study design in nature. The majority of meat samples were investigated from beef only (Abdissa et al, 2017;Alemu & Zewde, 2012;Atnafie et al, 2017;Bedasa et al, 2018;Beyi et al, 2017;Dagnachew, 2017;Garedew et al, 2015a;Garedew et al, 2015b;Gebretsadik et al, 2011;Abunna et al, 2016;Kore et al, 2017;Mengistu et al, 2017;Muluneh & Kibret, 2015;Wabeto et al, 2017;Adugna et al, 2018). The rest animal species were goat (Dulo, 2014;Dulo et al, 2015;Ferede, 2014), sheep (Mulu & Pal, 2016), and others (Ejo et al, 2016;Kebede et al, 2014;Senait & Moorty, 2016;Azage & Kibret, 2017).…”
Section: Search Resultsmentioning
confidence: 99%
“…Vertebrate animal species are natural reservoirs for many pathogens that cause human infections after transmitted through food [ 33 ]. Food of animal origin particularly meat (beef, mutton, and pork), dairy products (milk, cheese, yoghurt, and ice cream), and eggs are the three ways by which people are exposed to pathogenic bacteria [ 19 ]. Due to their nutritional value, mainly high protein and lipid content, dairy products are a suitable growth environment for a range of microorganisms [ 34 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%
“…Several food materials including milk and dairy products [ 19 ], pork, beef, mutton, poultry, and eggs are common vehicles that are frequently implicated in Staphylococcal food poisoning [ 42 ]. Raw meat is a good medium for S. aureus survival and spread of drug-resistant S. aureus in the community [ 61 ].…”
Section: Food-borne Zoonotic Bacterial Pathogensmentioning
confidence: 99%
See 1 more Smart Citation